Application of Data Mining techniques for the development of new rock mechanics constitutive models - Miranda, Tiago F. S. (2013)
Data Mining (DM) techniques have been successfully used in many fields and more recently also in geotechnics with good results in different applications. They are adequate as an advanced technique for analysing large and complex databases that can be built with geotechnical information within the framework of an overall process of Knowledge Discovery in Databases (KDD). A KDD process is carried out in the context of rock mechanics using the geotechnical information of two hydroelectric schemes built in Portugal and at DUSEL (Deep Underground Science and Engineering Laboratory), USA. The purpose was to find new models to evaluate strength and deformability parameters and also empirical geomechanical indexes. Databases of geotechnical data were assembled and DM techniques used to analyse and extract new and useful knowledge. The procedure allowed developing new, simple, and reliable models for geomechanical characterization using different sets of input data which can be applied in different situations of information availability.